Framing real beauty: A framing approach to the effects of beauty advertisements on body image and advertising effectiveness. (June 2021) - de Lenne, Orpha; Vandenbosch, Laura; Smits, Tim; Eggermont, Steven
Highlights: We examined framing effects of ads with idealized vs. non-idealized models. The current study used a mixed (pre-post x groups) experimental design. No effects of framing (appearance/body functionality/personality) on body image. Focusing on body functionality instead of appearance benefits advertising results. This result can encourage beauty brands to stop using typical objectifying ads. Abstract: Current literature is inconsistent about the effects of idealized (i.e., thin) vs. non-idealized (i.e., average or plus-size) models on young women's well-being. This inconsistency may be explained by different frames (i.e., passive body, active body, and subject) surrounding beauty ad models. The current experimental study among 568 women aged 18–30 years ( M = 21.45, SD = 1.84) tested the effects of differently framed ads featuring idealized vs. non-idealized models on well-being and ad effectiveness while taking into account the mediating role of cognitive schemas and moderating role of thin-ideal internalization. Results showed that a passive body frame generated more appearance schemas compared to a subject frame. The effects of framing on body functionality schemas operated differently for idealized vs. non-idealized models. The passive body frame also induced inferior ad outcomes (i.e., lower attitudes to the advertisement and brand and lower purchase intent) compared to an active body frame. No other main framing effects nor moderating effects of thin-ideal internalization were found. These results for advertising outcomes can encourage beauty brands to stop using typical objectifying ads.